Incidência e soroprevalência da infecção por Toxoplasma gondii no município de Santa Cruz e análise imunogenética em pacientes com toxoplasmose ocular do estado do Rio Grande do Norte - Débora de Almeida Aloise (2016)
Toxoplasmosis is one of the most common parasitic infections worldwide and estimates of seroprevalence for human and animal populations vary widely even within the same region. Toxoplasmosis-related survey in the states of Northeastern Brazil are few and no studies has been found in the literature with regard to the municipality of Santa Cruz - RN. In this paper we analyzed the prevalence of Toxoplasma gondii infection in both humans and animals (dog, cat and chicken) of this municipality. The enzyme-linked immunosorbent assay (ELISA) to detect IgG showed that 66.2% of the human population had anti - T. gondii antibodies. IgM anti- T. gondii antibodies were identified in 4.0% of these volunteers, of which 22.1% had negative results IgG (IgM+/ IgG-), and 77.9% tested positive for both IgM and IgG (IgM+/IgG+). The avidity test, performed on positive IgG sera, associated with IgM antibodies identified 2% of volunteers with infection classified as recent. Risk factors associated with infection were identified through a questionnaire. The final model after multivariate logistic analysis thefollowing factors: age (> 45 years / OR 7.4; 95% CI, 3.7 to 14.8 range, p = 0.01), educational level (Illiterate / OR 2.8; 95% CI, 1.6 to 5.0 range; p = 0.00), number of cats in residence (> 3 cats / OR 2.0; 95% CI, 1.2-3 range, 5, p = 0.01), no water tank (OR 2.0; 95% CI, 1.4 to 3.1 range; p = 0.01) and ingestion of raw / unpasteurized milk (OR 2.0; 95% CI, 1.3 to 3.0 range; p = 0.01). After follow-up of seronegative volunteers forone year, approximately, the incidence rate of infection by T. gondii observed in this municipality was 6.8 / 1000 person / month. Serological tests to detect IgG antibodies performed in animals, present in the home the municipality of Santa Cruz, showed seroprevalence of 47.4% in chicken, 75.8% in dogs and 60.1% in cats. Except for dogs, infection with this protozoan showed statistical association with age (Chicken: age> 12months / OR 4.5; 95% CI, 1.5 to 13.5 range, p = 0.00 / Cat: age > 5 years / OR 3.4; 95% CI; range 1.4 to 8.3; p = 0.00). Toxoplasma gondii infection in humans is often subclinical, however can develop and present a clinical signs, especially with retinochoroiditis. The immune response probably has a role in the evolution of infection and, in this study, we found a statistical association between ocular toxoplasmosis andpolymorphism APEX1 gene (rs1130409). The logistic regression analysis showed increased the risk of developing eye injury in patients with polymorphic alleles (GG) or heterozygous (GT). No correlation was found in the population studied between MyD88 gene (rs7744) and eye injury. Also, no correlation was found between retinochoroiditis and the expression profile of the cytokines IL-4, IL-5, IL-17A, IFN- and TNF-.